Prevalence of and factors influencing vitamin D deficiency in paediatric patients diagnosed with cancer at northern latitudes. (18th March 2021) - Jackmann, Natalja; Gustafsson, Jan; Harila‐Saari, Arja; Ljungman, Gustaf; Nezirevic Dernroth, Dzeneta; Frisk, Per; Mäkitie, Outi
Abstract: Aim: To investigate the prevalence of vitamin D deficiency among children with non‐haematological malignancies and to explore possible causes of low vitamin D levels among these patients. Methods: We performed a cross‐sectional study of 458 children diagnosed with solid tumours, brain tumours, non‐Hodgkin lymphoma or Hodgkin disease at the University Children's Hospital, Uppsala, Sweden. Serum 25‐hydroxyvitamin D and parathyroid hormone levels were measured in samples taken at the time of cancer diagnosis and related to clinical data. Vitamin D deficiency was defined as a 25‐hydroxyvitamin D level below 50 nmol/L. Results: The prevalence rate of vitamin D deficiency among children with non‐haematological malignancies was 41%. There was no association between sex or diagnosis and vitamin D status. Vitamin D deficiency was more common among school children than preschool children (51% vs. 24%). Older age, season outside summer, and a more recent calendar year were significant predictors of lower 25‐hydroxyvitamin D. There was a significant, albeit weak, negative correlation between 25‐hydroxyvitamin D and parathyroid hormone. Conclusion: Vitamin D deficiency is common among children diagnosed with cancer, particularly among school‐aged children diagnosed outside summer. The prevalence appears to be increasing, underlining the need for adequate replacement of vitamin D in these patients.